2014
DOI: 10.11604/pamj.2014.19.181.4872
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia, obesity and other cardiovascular risk factors in the adult population in Senegal

Abstract: IntroductionAccording to the WHO, 50% of deaths worldwide (40.1% in developing countries) are due to chronic non-communicable diseases (NCDs). Of these chronic NCDs, cardiovascular diseases remain the leading cause of death and disability in developed countries. The Framingham study has shown the importance of hypercholesterolemia as a primary risk factor. In Senegal, the epidemiology of dyslipidemia and obesity are still poorly understood due to the lack of comprehensive studies on their impact on the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
6
16
6
Order By: Relevance
“…Furthermore, we found a significant positive correlation between SBP, DBP, MAP and triglycerides one hand, and SBP, DBP, MAP and total cholesterol on the other (P < 0.01). The results of our study are consistent with previous literature data on this aspect (18,26,28,29).…”
Section: Serum Lipidssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we found a significant positive correlation between SBP, DBP, MAP and triglycerides one hand, and SBP, DBP, MAP and total cholesterol on the other (P < 0.01). The results of our study are consistent with previous literature data on this aspect (18,26,28,29).…”
Section: Serum Lipidssupporting
confidence: 93%
“…The prevalence of h y p e r t r i g l y c e r i d a e m i a a n d hypercholesterolaemia were 11.70% and 51.94% respectively. Compared with the results of other authors, our results are similar to those of a Senegalese study (26). However, we recorded a wide disparity in the prevalence rates of h y p e r t r i g l y c e r i d a e m i a a n d hypercholesterolaemia compared with previous literature (4,18,(26)(27)(28).…”
Section: Serum Lipidssupporting
confidence: 88%
“…A repeated cross-sectional study reported an increase over time in the prevalence of hypercholesterolaemia in Dar es Salaam with a prevalence of 17% in 1987 vs 30% in 1998 in men, and 7% vs 50% in women 39. The prevalence of hypercholesterolaemia in our sample was higher than that reported by studies conducted between 2008 and 2014 in rural Uganda (3% men, 8% women),9 peri-urban Nigeria (2% men, 6% women)8 and blacks in urban South Africa (25% men, 23% women),41 but is lower than that reported in a study from Senegal (54% men, 61% women) that included both urban and rural participants 42…”
Section: Discussioncontrasting
confidence: 77%
“…22,23 By contrast in Senegal and in Nigeria reported a low prevalence of dyslipidemia (63.8%, 60.5%, respectively). 24,25 Therefore, the overall prevalence of dyslipidemia varies from one country to another. The increasing prevalence of dyslipidemia in this study may be attributed to the current trend toward urbanization and adoption of western diet and lifestyle which have inadvertently resulted in the higher incidence of type 2 diabetes mellitus with its attendant metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%